2009
DOI: 10.1002/asi.21079
|View full text |Cite
|
Sign up to set email alerts
|

Self sanction and regulative sanction against copyright infringement: A comparison between U.S. and China college students

Abstract: Worldwide losses due to the copyright infringement of intellectual property such as PC software, music recordings, and motion pictures continue at epidemic proportions in emerging countries. This article develops a research model for analyzing individual ethical decision making that is influenced simultaneously by two chief forces: regulative sanction and self sanction. In particular, we report on the differences between 241 U.S. and 277 China college students' self-reported copyright infringement behaviors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Students in university play a critical role in piracy due to the advances in peer-to-peer file sharing programs which have made it easy for students to illegally download and share copyrighted content via campus network [2]. According to [1], piracy on campus has gained abundant attention due to recent high profile lawsuits against developers of file sharing software.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students in university play a critical role in piracy due to the advances in peer-to-peer file sharing programs which have made it easy for students to illegally download and share copyrighted content via campus network [2]. According to [1], piracy on campus has gained abundant attention due to recent high profile lawsuits against developers of file sharing software.…”
Section: Introductionmentioning
confidence: 99%
“…However, software piracy has no definite definition under the law. According to [2], software piracy is a form of copyright infringement which can happen in higher institutions where peers usually share information with each other. Thus, the act of software piracy can be dealt with under the provision of copyright infringement.…”
Section: Introductionmentioning
confidence: 99%
“…Social sanction comes in three forms: regulative, normative, and cultural-cognitive (Gerlach, Kuo, & Lin, 2009). The regulative form is normally comprised of well established laws which are used to coerce society to conform.…”
Section: Social Influence and Normsmentioning
confidence: 99%
“…Educating users to be able to self-regulate regarding how they perceive and conform to copyright compliance is critical to any efforts to curb infringement. Comparing students from China and those from the United States, Gerlach, Kuo, & Lin (2009) found that students from the United States were able to exhibit higher levels of self-regulation efficacy when compared to those from China. As a result of more strict enforcement of copyright laws in the U.S., American students exhibited a higher level of perceived risk as compared to those from China, where enforcement is not as strict.…”
Section: Social Influence and Normsmentioning
confidence: 99%
See 1 more Smart Citation